Gross Anatomy of Cerebral Ventricles and Septum Pellucidum of Brain of Surti Buffalo (Bubalus bubalis) - Suman, Alka; Pandya, Sweta (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
he objective of the present work was to study the cerebral ventricles and its associated parts of brain of Surti buffalo (n=12), The cerebral ventricles included two lateral ventricles and third ventricle. The lateral ventricles were curved cavities presented large central part and three horns within the cerebral hemispheres. The third ventricle was an annular space on the periphery of inter-thalamic adhesion between two thalami. The mean length and width of central part of lateral ventricle were 4.78±0.07 and 1.49±0.07 cm, respectively. The septum pellucidum was thin translucent membrane of two laminae which separates two lateral ventricles. The mean values of length and height of septum pellucidum were 3.6±0.12 and 0.52±0.04 cm, respectively. The cavum septum pellucidum was a small space found between two laminae of septum pellucidum. are concerned with the production and circulation The ventricular system of the brain is a set of four interconnected cavities (ventricles), where the cerebrospinal fluid (CSF) is produced from the choroid plexus which bathes the central nervous system (Crisan and Chawla, 2016). The ventricular system is composed of the two largest lateral ventricles in the cerebrum; the third ventricle is in the diencephalon of the forebrain between the right and left thalamus; and the fourth ventricle is located at the back of the pons and upper half of the medulla oblongata of the hind brain (Mortazavi et al., 2014). The ventricles of cerebrospinal fluid. The Surti is a breed of water buffalo found in the Charottar tract of Gujarat (Banerjee, 2014). There is no data established on the topography and morphometry of cerebral ventricles and septum pellucidum of brain of these animals. Hence, the present work was aimed to study the cerebral ventricles and its associated parts of brain of Surti buffalo.